الاستدلال بالنصوص القرآنية على حجية خبر الواحد عند الشيعة الامامية (آية النبـأ أنموذجا) - الزاهد محسن شعين عبيد (lark, 2019)
Abstract The magnanimous Islamic legislation is an integrated system for human life. The jursts throughout the ages can find what the human being needs depending on the sources of legislation. The Holy Koran is the first source of Islamic legislation as well as the Sunnah. The other sources of legislation such as consensus and mind solve the cases that have no legislatiove rules in Koran and Sunna. The Sunna, which is attributed to the Prophet or to the infallible Imams, explains the Holy Koran. The words and deeds of infallible Imams are an extension to the words and deeds of the Prophet . The research consists of introduction, preface, and three section. The preface is dealt with the news per trust in Islamic legislation and the opinions of the jurists about it. The fiest section was analytic study to the holy text and its vocabulary . The second section is dealt with the evidence of the news per trust. Finally, the conclusion , the results , a list of margins, a list of references and resources, and an English abstract.